Fabrication of ammonia gas sensor based on polyaniline/mussel shell composite - Albar, M.M.J. (Akademi Sains Malaysia, 2020)
Commercial polyaniline/mussel shell (cPANI/MS) and lab-synthesized polyaniline/mussel shell (sPANI/MS) composites were prepared in order to study the sensor performances in ammonia gas detection. Both cPANI/MS and sPANI/MS were characterized using Fourier transform infrared (FTIR) and Ultraviolet-Visible (UV-Vis) spectroscopy techniques. FTIR confirmed the main characteristic peaks of PANI at ~1462 cm-1 and ~1599 cm-1 which indicates benzenoid and quinoid ring, respectively. Besides that, the peaks in the range of 1417-1453 cm-1 indicates the presence of calcium carbonate within the PANI matrix. UV-Vis spectra further confirmed both PANI composites are in the doped state by exhibiting the characteristic peak at ~790-820 nm. Sensor performance of cPANI/MS was studied in different concentrations of ammonia gas (10-100 ppm). In conclusion, it is possible to prepare waste mussel shells as a composite material with PANI in order to apply it as a gas sensor. Â© 2020 Akademi Sains Malaysia.